2000
DOI: 10.1046/j.1523-1755.2000.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin reduces renal oxidative DNA and tissue damage during phenylhydrazine-induced hemolysis

Abstract: Haptoglobin appears to play an important physiological role as an antioxidant, particularly during hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 50 publications
3
82
0
3
Order By: Relevance
“…Haptoglobin appears to play an important physiological role as an antioxidant, particularly during haemolysis, i.e. the breakdown of red blood cells (Lim et al, 2000). Exercise-induced haemolysis is well documented in humans (Sentürk et al, 2005), and has been suggested to occur in birds (Landys-Ciannelli et al, 2002;Piersma et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin appears to play an important physiological role as an antioxidant, particularly during haemolysis, i.e. the breakdown of red blood cells (Lim et al, 2000). Exercise-induced haemolysis is well documented in humans (Sentürk et al, 2005), and has been suggested to occur in birds (Landys-Ciannelli et al, 2002;Piersma et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The covalent Hb/haptoglobin complex has long been considered the major pathway for directing CF-Hb clearance (1,5,41). Although studies (3,8,33) have demonstrated that haptoglobin limits Hb-induced hypertension and renal damage, a recent study (3) showed that haptoglobin did not decrease the half-life (t 1/2 ) of CF-Hb in the circulation or inhibit the ability of CF-Hb to react with NO. Additionally, CF-Hb clearance in haptoglobin-null mice was not altered compared with wildtype mice (32).…”
mentioning
confidence: 99%
“…The formation of a complex between Hp and Hb also prevents Hb from passing through the glomeruli. Thus, mice lacking Hp display renal failure (4). Whether lower vertebrates also use Hp as a protective measure against the harmful effects of free Hb is not known.…”
mentioning
confidence: 99%